Evaluation the Upper Structure of Railway Bridge Complex Profile Steel Frame - Muhammad Adib; Wahyu Tamtomo; David Malaiholo (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2021)
In order to support learning facilities, The Indonesian Railway Polytechnic Madiun plans to build a Railway Bridge, where the bridge is the dismantling of the Kertosono-Sembung BH-259 railway bridge. Before construction needs to be done an evaluation of the skeletal structure of the railway bridge.  Evaluation of the structure of the railway bridge begins with the identification of the profile of the bridge structure, the selection of loading in accordance with the means that will pass through, then continued by determining the combination of loading and modeling and running using structural analysis software.  Loading refers to PM No.60 Year 2012, while the combination of loading refers to the Indonesian Railway Technical Standard for Steel Bridge Structure (DJKA, 2006). The results of the analysis and calculation showed that the maximum deflection of bridge girder occurring at δ = 0.416 cm occurred in a joint located in the middle of the railway bridge and met the requirements of δ  ≤  δ' but based on the analysis of the dimensions of the bridge structure capacity in Software analys structure the maximum capacity ratio value at the transverse bridge girder of 2,286 exceeded the required capacity ratio value requirement. So it is necessary to re-analyze to determine the strengthening on the overstressed profile.